Ocenjevanje kakovosti stoječih dreves - Krajnc, Luka (Gozdarski vestnik, 2022)
Monitoring of wood quality begins in the forest, since knowing the current status represents one of the key factors in directing further forest development towards higher quality of wood. However, directing forest development towards a higher wood quality and thereby its higher added value demands, to start with, measurability of the quality. Without it, the assessment of the eventual measures in the stand is almost impossible or, at least, very difficult. The currently used methodology for estimating the stem quality of standing trees on the permanent sample plots of the Slovenia Forest Service is based on the invalid sawmill standards and should be updated for general use in forestry. In this article, we briefly describe the existing methodology, present the review of the existing methodologies for estimating the stem quality of standing trees in diverse countries, and suggest a new methodology for estimating the stem quality of the trees. The basic goal of the described work was the development of the methodology with which we could objectively compare the stem quality from different stands, and which would enable assorting these trees' volumes into the potential forest wood assortments. The use of the suggested quality scale for describing the stem quality of the standing trees can represent one of the accessories for deciding where and how much time or assets should be invested in silvicultural measures in an individual stand.
Keywords: drevesa; gozdnolesni sortimenti; kvaliteta debla; sortimentacija stoječega drevesa; stoječa drevesa